432Recurrent stillbirth: a population-based study from South Australia. (2nd September 2021) - Smithers, Lisa; Lamont, Kathleen; Bhattacharya, Sohinee
Abstract: Background: In high-income countries, stillbirth is a relatively rare event occurring in < 1% of pregnancies. Recurrent stillbirth is even rarer. Our objective was to explore the prevalence of stillbirth and recurrent stillbirth, factors associated with stillbirth and whether a stillbirth in first pregnancy influences the time to subsequent pregnancy. Methods: This population-based study involved routinely-collected administrative data on singleton births in South Australia from 1998 to 2015 (n = 333, 785). Stillbirth was defined as pregnancies >20 weeks gestation or weighing >400 grams. Univariable and multivariable logistic regression was used to explore associations between sociodemographic factors and stillbirth. Cox proportional hazard was used to explore time to pregnancy. Results: 0.7% of all first pregnancies and 0.6% of all second pregnancies were stillbirths. Of women in their second pregnancy, <10 experienced recurrent stillbirth. In univariable analyses, higher odds of stillbirth in second pregnancies were associated with younger and older maternal age (<20 or ≥ 40 years), being single, unemployed, smoking, shorter inter-pregnancy intervals and numerous medical conditions (e.g. diabetes or hypertension). Multivariable models were unstable due to too few data. The hazard ratio for women who previously experienced a stillbirth compared with livebirth was 1.14 (95%CI 0.39, 3.32). Conclusions: Studying recurrent stillbirth is especially difficult due to the rare nature of the problem, limiting progress on developing evidence-based advice for women who experience stillbirth in their first pregnancy. Key messages: Recurrent stillbirth is challenging to study due to the rareness of the problem but could be addressed by careful pooling of large administrative datasets.